Microbial treatment of alcoholic liver disease: A systematic review and meta-analysis - Wang, Qinjian; Shi, Jiangmin; Zhao, Min; Ruan, Gaoyi; Dai, Zebin; Xue, Yilang; Shi, Dibang; Xu, Changlong; Yu, Ouyue; Wang, Fangyan; Xue, Zhanxiong (Frontiers in Nutrition, 2022)
Background and aims: Alcoholic liver disease (ALD) is characterized by impaired liver function due to chronic alcohol consumption, even fatal in severe cases. We performed a meta-analysis to determine whether microbial agents have therapeutic potential for ALD and elucidate the underlying mechanisms.Methods and results: Forty-one studies were eligible for this meta-analysis after searching the PubMed, Cochrane, and Embase databases. The combined analysis showed that microbial therapy significantly decreased hepatic enzymatic parameters, including alanine transaminase (standardized mean difference [SMD]: -2.70, 95% confidence interval [CI]: -3.33 to -2.07), aspartate aminotransferase (SMD: -3.37, 95% CI: -4.25 to -2.49), γ-glutamyl transpeptidase (SMD: - 2.07, 95% CI: -3.01 to -1.12), and alkaline phosphatase (SMD: -2.12, 95% CI: -3.32 to -0.92). Microbial agents were also effective in reducing total cholesterol (SMD = -2.75, 95%CI -4.03 to -1.46) and triglycerides (SMD = -2.58, 95% CI: -3.13 to -2.03). Microbial agents increased amounts of the beneficial flora Lactobacillus (SMD: 4.40, 95% CI: 0.97 to 7.84 ) and Bifidobacteria (SMD: 3.84, 95% CI: 0.22 to 7.45) , Bacteroidetes (SMD: 2.51, 95% CI: 0.29 to 4.72) and decreased harmful Proteobacteria (SMD: -4.18, 95% CI: -6.60 to -1.77), protecting the integrity of the intestinal epithelium and relieving endotoxin (SMD: -2.70, 95% CI: -3.52 to -2.17) into the portal vein, thereby reducing the production of inflammatory factors such as tumor necrosis factor-α (SMD: -3.35, 95% CI: -4.31 to -2.38), interleukin-6 (SMD: -4.28, 95% CI: -6.13 to -2.43), and interleukin-1β (SMD: -4.28, 95% CI: -6.37 to -2.19). Oxidative stress was also relieved, as evidenced by decreased malondialdehyde levels (SMD: -4.70, 95% CI: -6.21 to -3.20). Superoxide dismutase (SMD: 2.65, 95% CI: 2.16 to 3.15) and glutathione levels (SMD: 3.80, 95% CI: 0.95 to 6.66) were elevated.Conclusion: Microbial agents can reverse dysbiosis in ALD, thus significantly interfering with lipid metabolism, relieving inflammatory response and inhibiting oxidative stress to improve liver function.